Sport governance as global governance: theoretical perspectives on sport in the international system - Jedlicka, S. R. (International Journal of Sport Policy and Politics, 2018)
International sport governance is often described as both a significant and unique part of international politics. Simultaneously, proponents of this view lament the lack of (especially academic) attention paid to international sport governance as a political phenomenon. In this essay, the author argues that remedying this problem requires an understanding of sport as a product of the international system, and that the existing system of transnational sport governance organisations should be studied in much the same way as other international governance institutions, such as the United Nations, the World Health Organization and the Organisation for Economic Cooperation and Development. This conceptualisation of international sport governance as an institution is used to demonstrate how paradigms and theoretical frameworks from the field of international relations (IR) can be usefully applied to international sport governance research. Integrating IR theory with sport governance research can enhance the understanding of international sport`s political status and impacts, as well as the nature of international institutions more generally.